2023
DOI: 10.1039/d3tc00065f
|View full text |Cite
|
Sign up to set email alerts
|

Toward narrowband emission: the chemical strategies for modifying boron-based luminescent materials

Abstract: High-definition display-based organic light-emitting diodes (OLEDs) call for narrowband emission from each pixel. Recently, the boron-based thermally activated delayed fluorescence (TADF) emitters soon attract the broad attention of the OLEDs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Recently, studies focusing on the structure-function relationship of boron (B)-based luminescent materials gained tremendous impetus in optoelectronics and sensors. [7][8][9][10][11][12] The boron (B) atom possess enormous advantages, such as Lewis acid nature, high reactivity, energy carrier ability, and high stability indicating their versatility. [7,12] In 2012, Yamaguchi and co-workers demonstrated that the planarized triarylboranes containing vacant P z orbital, can be stabilized by the structural constraints without steric hindrance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies focusing on the structure-function relationship of boron (B)-based luminescent materials gained tremendous impetus in optoelectronics and sensors. [7][8][9][10][11][12] The boron (B) atom possess enormous advantages, such as Lewis acid nature, high reactivity, energy carrier ability, and high stability indicating their versatility. [7,12] In 2012, Yamaguchi and co-workers demonstrated that the planarized triarylboranes containing vacant P z orbital, can be stabilized by the structural constraints without steric hindrance.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The boron (B) atom possess enormous advantages, such as Lewis acid nature, high reactivity, energy carrier ability, and high stability indicating their versatility. [7,12] In 2012, Yamaguchi and co-workers demonstrated that the planarized triarylboranes containing vacant P z orbital, can be stabilized by the structural constraints without steric hindrance. Following this work, tricoordinate B-based π-systems got astonishing attention in the development of functional materials with excellent luminance and acceptor characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Following this pioneering work, numerous B, N-doped PAHs with unique structural features of suitably positioned electron-donating N atoms and electron-withdrawing B atoms are reported. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The ortho-positioned boron and nitrogen atoms having opposite resonance effects induce the localization and separation of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) on different atoms, resulting in a small singlettriplet splitting energy (DE ST ) required for a reverse intersystem crossing (RISC) process in TADF materials. 3 Moreover, such materials with multiple resonance (MR) properties minimize the bonding/anti-bonding characters and molecular relaxations upon excitation, which is desired for narrowband emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of HOMO–LUMO successfully decreases the exchange interaction in the T 1 state, which can directly minimize the S 1 –T 1 gap according to quantum chemistry theory. However, unfortunately, such a strategy will lead to a significant structural relaxation in the S 1 state and then result in an unwanted broadband emission which can significantly reduce the external quantum efficiency (EQE) of the OLED displays. , In 2016, Hatakeyama et al reported a kind of novel multiresonance thermally activated delayed fluorescence (MR-TADF) molecule, DABNA-1 and DABNA-2 . Therein the opposite resonance effects of electron-withdrawing and -donating atoms (B and N) are used to achieve HOMO–LUMO separations and ultrapure narrowband emissions. , Therefore, they become the most promising candidates for TADF materials. , After a lot of research, it is found that parent molecules to construct MR-TADF are very scarce besides DABNA-1 and DABNA-2 species, which greatly limited its practical application. Furthermore, the emission color of MR-TADF is also limited due to the lack of rich parent molecules which can determine the electronic properties of S 1 . ,,, Therefore, the search for a new generation of parent molecules is particularly important for the development of TADF materials. By inspecting the HOMO and LUMO of MR-TADF molecules, it is found that these orbitals have nonbonding characteristics, which is responsible for narrowband emissions. Inspired by it, diradicals born with nonbonding orbitals instantly come to mind, and they have abundant and diverse parent molecules.…”
mentioning
confidence: 99%